P587 Disease severity in the INFLAMMATORY BOWEL DISEASES: Do patients and physicians agree?. (21st January 2022) - Timmer, A; de Sordi, D; Neuser, J; Seibel, K; Hensel, A; Schmidt-Lauber, M; Allgayer, H; Klebl, F; Obermeier, F; Jessen, P; Schnoy, E; Helwig, U; et al.
Abstract: Background: Evaluation of disease severity (DS) in the Inflammatory Bowel Diseases (IBD) requires comprehensive consideration of disease course and health status of individual patients. It is not clear how well physician assessment covers disease impact as perceived by patients. We compared patient and physician global assessment of disease severity in relation to standardized assessment using a clinical disease severity score (DSI, Siegel 2018). Methods: Patients with ulcerative colitis (UC) and Crohn's disease (CD) were prospectively recruited from the national patient organization (DCCV) and by participating physicians. Physicians (IBD experts) were approached via the DCCV advisory board and other professional contacts. Both groups graded disease severity for a random selection of written standard short cases (1 page, maximum 5 CD, 3 UC) on a simple visual analogue scale (VAS) (online survey). For analysis, VAS were transferred to a 0 (minimal severity) to 100 (maximal severity) scale, in analogy to the range of the DSI. We present graphs of mean scores by rater group with 95% CI. Differences between mean patient and physician assessments were calculated per case. In addition, we examined the difference from the DSI. Results: We included 824 ratings from 319 patients (168 CD, 151 UC), and 143 ratings from 34 physicians (20 ISS, 14 external)(recruitment ongoing). UC cases received on average 124 patient ratings (range 122–125), and 21 physician ratings (range 17–26). Means from both rater groups discriminated well between disease severity as scored by the DSI. Mean physician ratings were consistently and substantially lower than patient ratings for all three UC cases. Differences between means ranged from 8.5 (95% CI 0.5 to 16.5) for mild disease to 10.1 (95% CI 1.3 to 18.9) for moderate disease (p < 0.001) (Figure 1). In contrast, deviations from the DSI did not show a clear pattern. CD cases were rated by a mean of 91 patients (77–125) and 16 physicians (13–21). Mean physician and mean patient ratings were very close, in particular in those with medium DSI (Figure 2). Conclusion: Physicians agreed, on average, very well with patient grading on disease severity grading of exemplary cases of CD. Lower scores were given for UC cases, and mild CD, but the overall trend remained intact. In contrast, correlation with DSI scores was poor and will need further analysis.